Swimming Away the Damage: Exercise Combats Alcohol-Induced Liver Stress in Wistar Rats - I, Abdul-kareem Y.; C, Uchendu; G, Yilgwan; P, Nyango; M, Usman Y.; Z, Galam N. (Darul Yasin Al Sys, 2024)
This study investigated the impact of forced swimming exercise on alcohol-induced oxidative stress biomarkers and liver histo-architecture in Wistar rats (mean weight 150 to 200g). The rats were randomly assigned to four groups of five: normal control, exercise only, alcohol only, and exercise plus alcohol. The control group received 0.9% saline for 5 days a week over 12 weeks. The exercise group underwent forced swimming for 5 minutes daily, 5 days a week, for 12 weeks. The alcohol group was given 20% ethanol orally at a dose of 2.0 g/kg body weight. The exercise plus alcohol group received both treatments as described for the exercise and alcohol groups. At the end of the exposure period, all animals were euthanized, and blood and liver tissue samples were collected for analysis of oxidative stress biomarkers (SOD, CAT, GPx, and MDA) and liver histo-architecture. The ethanol-exposed group showed significantly elevated oxidative stress markers, whereas the normal, exercise, and exercise plus alcohol groups exhibited decreased levels. Marked hepatocellular necrosis and perivascular inflammation were observed in the ethanol group, along with moderate central vein congestion. In contrast, the normal and exercise groups displayed normal hepatocellular architecture with no inflammatory cells and clear central veins. The exercise plus alcohol group showed largely normal liver architecture, with very mild necrotic cells, no inflammatory cells, and a clearly visible central vein, indicating that exercise mitigated alcohol-induced liver changes in adult male Wistar rats. These findings suggest that exercise training can alleviate oxidative stress and prevent liver architecture damage following chronic alcohol consumption, potentially helping to prevent liver failure and hepatocellular carcinoma.